Immunodiagnostic Technologies from Laboratory to Point-Of-Care Testing - Suman P.; Chandra P. (My University, 2025)
This book presents the timeline of immunodiagnostics evolution, including advancements in immunological/nucleic acid probes, assay design, labelling techniques, and devices for signal transduction and acquisition. In the past few years, enzyme and nanocatalyst-based immune assays have undergone numerous modifications to enhance their sensitivity and potential for automation. Further, to reduce production costs and the use of laboratory animals, engineering small antibodies and nucleic acid probes (aptamers) has become increasingly popular in the development of novel and powerful bioassays. In light of the notable advancements in immunodiagnostics, this book highlights the combined efforts of clinicians, biotechnologists, material scientists, nanotechnologists and basic scientists in a coherent and highly structured way. The book takes readers on the journey of immunodiagnostic technologies, from their introduction to the present. © Springer Nature Singapore Pte Ltd. 2021.